Productivity and Profitability of Four Crops Based Cropping Pattern in Cumilla Region of Bangladesh (The Agriculturists, 2018)
Field experiment was conducted at the farmers' field of Amratoli, Barura multi location testing site of Cumilla during 2014-15 and 2015-16 to increase cropping intensity and productivity by inclusion of T. Aus in existing cropping pattern. Thus experiment variables were F: Existing cropping pattern (Potato -Boro-Fallow-T. Aman) and FA: Alternate cropping pattern (Potato- Boro- T. Aus- T.Aman). Research result indicated that rice equivalent yield (REY) in alternate cropping pattern was 43.46 t ha-1, which is 25.90% higher over existing pattern (34.52 t ha-1). Higher gross return (Tk. 651900 ha-1), gross margin (Tk. 416520 ha-1) and higher marginal benefit cost ratio (2.77) obtained from alternate cropping pattern messaged that this pattern may be recommended to other extrapolation areas of Cumilla region.The Agriculturists 2018; 16(2) 88-92